Identification of policies for a sustainable legal trade in rhinoceros horn based on population projection and socioeconomic models - Di Minin, Enrico (Conservation biology : the journal of the Society for Conservation Biology, 2015)
© 2014 The Authors. Conservation Biology published by wiley Periodicals, Inc., on behalf of the Society for Conservation Biology.